Innovación en la competitividad de la industria manufacturera de Tacna: un análisis de las pymes en 2024 - Carrillo Zavala, Hugo Abel (2025)
Objective: The main objective of this research was to determine the influence of business innovation on the competitiveness of small and medium-sized enterprises (SMEs) in the manufacturing industry in the Tacna region by 2024. Method: A non-experimental, cross-sectional research design with a quantitative approach was used. The study population consisted of 74 SMEs, using a census sampling. To evaluate the relationship between innovation and competitiveness, Spearman's Rho correlation and the ordinal regression model were applied. Results: The analyses showed that business innovation has a significant positive relationship with competitiveness. Innovation in processes and operations obtained the highest correlation, with a coefficient of 75.83%, followed by technological innovation with 58% and organizational management with 61.9%. Sustainability and social responsibility had a lower influence, with 39.2%. Conclusions: It is concluded that SMEs that implement business innovation strategies significantly improve their competitiveness. This strengthening is reflected in the optimization of processes, products, and organizational structures, allowing companies to better adapt to market requirements. Future studies are recommended to delve deeper into the dimensions of innovation and its impact on competitiveness.